Acemetacin cocrystal structures by powder X-ray diffraction - Bolla, Geetha; Chernyshev, Vladimir; Nangia, Ashwini (Iucrj, 2017)
Cocrystals of acemetacin drug (ACM) with nicotinamide (NAM), p-aminobenzoic acid (PABA), valerolactam (VLM) and 2-pyridone (2HP) were prepared by melt crystallization and their X-ray crystal structures determined by high-resolution powder X-ray diffraction. The powerful technique of structure determination from powder data (SDPD) provided details of molecular packing and hydrogen bonding in pharmaceutical cocrystals of acemetacin. ACM-NAM occurs in anhydrate and hydrate forms, whereas the other structures crystallized in a single crystalline form. The carboxylic acid group of ACM forms theacid-amide dimer three-point synthon R-3(2)(9) R-2(2)(8) R-3(2)(9) with three different syn amides (VLM, 2HP and caprolactam). The conformations of the ACM molecule observed in the crystal structures differ mainly in the mutual orientation of chlorobenzene fragment and the neighboring methyl group, being anti (type I) or syn (type II). ACM hydrate, ACM-NAM, ACM-NAM-hydrate and the piperazine salt of ACM exhibit the type I conformation, whereas ACM polymorphs and other cocrystals adopt the ACM type II conformation. Hydrogen-bond interactions in all the crystal structures were quantified by calculating their molecular electrostatic potential (MEP) surfaces. Hirshfeld surface analysis of the cocrystal surfaces shows that about 50% of the contribution is due to a combination of strong and weak O center dot center dot center dot H, N center dot center dot center dot H, Cl center dot center dot center dot H and C center dot center dot center dot H interactions. The physicochemical properties of these cocrystals are under study.